SARS‐CoV‐2 spike protein aggregation is triggered by bacterial lipopolysaccharide. Issue 19 (11th September 2022) - Petrlova, Jitka; Samsudin, Firdaus; Bond, Peter J.; Schmidtchen, Artur
Abstract : SARS‐CoV‐2 spike (S) protein is crucial for virus invasion in COVID‐19. Here, we showed that lipopolysaccharide (LPS) can trigger S protein aggregation at high doses of LPS and S protein. We demonstrated the formation of S protein aggregates by microscopy analyses, aggregation and gel shift assays. LPS at high levels boosts the formation of S protein aggregates as detected by amytracker and thioflavin T dyes that specifically bind to aggregating proteins. We validated the role of LPS by blocking the formation of aggregates by the endotoxin‐scavenging thrombin‐derived peptide TCP‐25. Aggregation‐prone sequences in S protein are predicted to be nearby LPS binding sites, while molecular simulations showed stable formation of S protein–LPS higher‐order oligomers. Collectively, our results provide evidence of LPS‐induced S protein aggregation. Abstract : Bacterial lipopolysaccharide (LPS) plays a central role in SARS‐CoV‐2 spike protein‐induced inflammation. We have previously shown that spike protein binds to LPS. Here, we reveal that at high micromolar concentrations of LPS and spike protein, the spike–LPS complex forms large aggregates. The study complements our previous findings that low subnanomolar concentrations of spike and LPS boost the Toll‐like receptor 4 (TLR4)‐mediated inflammatory response.